Balancing of Coupled Piezoelectric NEMS Resonators - Fan, J.; Lemonde, J.; Maillard, D.; Käppeli, M.; Villanueva, L. G. (Frontiers in Mechanical Engineering, 2021)
Micro and Nano Electro Mechanical systems (M/NEMS) have a lot of potential to be used for sensing in different schemes and operation modes. We focus here on the use of coupled resonators for sensing and address the major limitation that these systems face, which stems from a compromise between dynamic range and responsivity. When the system becomes unbalanced, the responsivity drops. To solve this issue, we propose the use of piezoelectric-based stress tuning of the stiffness of the resonators in order to rebalance the system of resonators. With this approach we expect to be able to extend the dynamic range of such systems by some orders of magnitude.